DETERMINING THE DENSITY AND MOLAR MASS OF AIR IN A HOME EXPERIMENT - Serhii Podlasov (Фізико-математична освіта)
Formulation of the problem. Experimental research is an integral part of physics education. During distance learning, students can carry out hands-on experiments only at home. Modern smartphones, equipped with various sensors, offer significant capabilities  for  this  purpose.  The   literature   offers   quite   extensive   descriptions   of   experiments   aimed   at   determining mechanical, acoustic, and optical quantities using smartphones. At the same time, insufficient attention has been paid to determining gas parameters that can be measured using the pressure sensor embedded in smartphones. Therefore, the relevant task is to develop a methodology for experimenting to determine the density of air and its molar mass at home using a pressure sensor.